Assessment of PD‐L1 Expression on Circulating Tumor Cells for Predicting Clinical Outcomes in Patients with Cancer Receiving PD‐1/PD‐L1 Blockade Therapies. (28th September 2021) - Tan, Zhaoli; Yue, Chunyan; Ji, Shoujian; Zhao, Chuanhua; Jia, Ru; Zhang, Yun; Liu, Rongrui; Li, Da; Yu, Qian; Li, Ping; Hu, Zhiyuan; Yang, Yanlian; et al.
Abstract: Background: Programmed death‐1 (PD‐1) and programmed death‐ligand 1 (PD‐L1) blockade immunotherapies have changed the landscape of cancer therapy. However, the main limitation of these therapies is the lack of definitively predictive biomarkers to predict treatment response. Whether PD‐L1 expression on circulating tumor cells (CTCs) is associated with the clinical outcomes of immunotherapy remains to be extensively investigated. Materials and Methods: One hundred fifty‐five patients with different advanced cancers were enrolled in this study and treated with anti‐PD‐1/PD‐L1 monoclonal antibodies. Using the Pep@MNPs method, CTCs were isolated and enumerated. The PD‐L1 expression levels were analyzed by an immunofluorescence assay for semiquantitative assessment with four categories (negative, low, medium, and high). Results: Prior to immunotherapy, 81.93% (127/155) of patients had PD‐L1‐positive CTCs, and 71.61% (111/155) had at least one PD‐L1‐high CTC. The group with PD‐L1‐positive CTCs had a higher disease control rate (DCR) (71.56%, 91/127), with a DCR of only 39.29% (11/28) for the remaining individuals ( p  = .001). The objective response rate and DCR in PD‐L1‐high patients were higher than those in the other patients (32.44% vs. 13.64%, p  = .018 and 75.68% vs. 40.91%, p  < .0001, respectively). The reduction in the counts and ratios of PD‐L1‐positive CTCs and PD‐L1‐high CTCs reflected a beneficial response to PD‐1/PD‐L1 inhibitors. Furthermore, patients with PD‐L1‐high CTCs had significantly longer progression‐free survival (4.9 vs. 2.2 months, p  < .0001) and overall survival (16.1 vs. 9.0 months, p  = .0235) than those without PD‐L1‐high CTCs. Conclusion: The PD‐L1 level on CTCs may serve as a clinically actionable biomarker for immunotherapy, and its dynamic changes could predict the therapeutic response. Implications for Practice: This study was designed to investigate the role of programmed death‐ligand 1 (PD‐L1) expression on circulating tumor cells in predicting and monitoring response to programmed death‐1 (PD‐1)/PD‐L1 blockade immunotherapies in patients with advanced cancer. The results of the study showed that PD‐L1‐high‐expression circulating tumor cells (CTCs) were both a predictive biomarker and a prognostic factor in patients with advanced cancer treated with anti‐PD‐1/PD‐L1 monoclonal antibodies. These observations suggest that PD‐L1 level on CTCs is a potential clinical biomarker for immunotherapy. Abstract : This study investigated the role of PD‐L1 expression on circulating tumor cells in predicting and monitoring response to PD‐1/PD‐L1 blockade immunotherapies in patients with advanced cancer.